Tanggung Jawab Administrasi Pemerintah dalam Era Digital: Analisis Implementasi Sistem OSS-RBA dalam Penyelenggaraan Perizinan Berbasis Risiko - Silalahi, Wilma; Putri, Mutiara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The digital transformation of public administration in recent decades has reshaped government service delivery, particularly through the adoption of technology as a tool to enhance transparency, efficiency, and accountability. The implementation of the Online Single Submission–Risk Based Approach (OSS-RBA) represents Indonesia’s strategic effort to create an integrated licensing framework aligned with the principles of good governance. This study aims to analyze the forms of administrative responsibility in digital-based licensing services under OSS-RBA and examine the accountability mechanisms applicable when system failures affect legal certainty for business actors. The research employs a normative juridical method using statutory, conceptual, and case approaches through the examination of regulations, doctrines, and administrative court decisions. The findings indicate that digitalization does not alter the core of governmental responsibility, as every decision generated by the system is legally attributed to the competent administrative authority. The implementation of OSS-RBA still faces obstacles such as system errors, data inconsistencies between institutions, and delays in technical verification, all of which directly affect legal certainty and the quality of public services. Furthermore, internal and external oversight mechanisms are not yet fully effective in preventing maladministration, including unreasonable delays and inaccuracies in automated decision-making. The study also shows that business actors require more responsive administrative remedies to prevent technological risks from shifting entirely onto them. Therefore, this research concludes that the effectiveness of OSS-RBA depends on strengthening institutional capacity, harmonizing regulations, and ensuring the consistent application of good governance principles throughout all stages of digital licensing administration.